Dukungan Keluarga pada Ibu Postpartum terhadap Kejadian Postpartum Blues - Rina Nuraeni; Ruri Yuni Astari; Aat Agustini; Pebriyanti Wulandari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the relationship between family support for postpartum mothers and the incidence of postpartum blues at Gunung Jati Hospital, Cirebon. The method used is correlational research with a cross-sectional approach. The results showed that less than half (40.0%) of postpartum mothers received low family support and less than half (42.9%) of postpartum mothers experienced postpartum blues with r-value = 0.001. In conclusion, there is a relationship between family support for postpartum mothers and the incidence of postpartum blues at Gunung Jati Hospital, Cirebon. Keywords: Family Support, Postpartum, Postpartum Blues